STUDENTS’ PERCEPTION ON THE FACILITATION STRATEGIES PROVIDED BY TEACHERS IN ASYNCHRONOUS ONLINE DISCUSSION - Dewi, Gusti Putu Rustika; Santosa, Made Hery (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
Facilitation strategies provided in asynchronous online discussion environment becomes essential aspects in learning. This present study was a case study aimed at exploring EFL students’ perception on facilitation strategies provided in asynchronous online discussion in terms of monitoring, feedback and scoring rubric implemented in the online discussion. Questionnaire was administered to one hundred students and interview was conducted to six voluntary students who were enrolled in courses with asynchronous online discussion. The result indicated that students’ perception on the facilitation strategies provided in asynchronous online discussion was neutral which indicated that facilitation provided by teachers did not become the main preference for the students in asynchronous online discussion. Students perceived teachers’ monitoring positively since the students need more guidances to understand the concept as well as to indicate that their participation is apprecited by the teachers. Meanwhile, students had neutral perception toward feedback and scoring rubric provided in asynchronous online discussion. They perceived that feedback and scoring rubric are not essential elements that influence their participation in asynchronous online discussion. Furthermore, it implied that the facilitation strategies provided in asynchronous online discussion has to enable teacher to check students progress and to motivate students to engage in asynchronous online discussion.